189k views
0 votes
Solve for t. f(t)=-16t^2+576​

User Ruuska
by
5.4k points

1 Answer

0 votes

Answer: t^2=-f-576/16

Explanation:

Step 1. Switch the equation around:

-16t^2+576=f

Step 2. Subtract 576 from each side:

-16t^2+576-576=f-576

Step 3. Now simplify:

-16t^2=f-576

Step 4. Divide everything now by -16:

-16t^2/-16=f/-16-576/-16

Step 5. Simplify again:

t^2=-f-576/16

Hope I could help! :)

User Joshfarrant
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.